Analysis of the Use of Visual Scaffolding Media in Understanding the Practice of Prayer among Students with Mild Intellectual Disabilities at Mutiara Bunda Special School, Cirebon - Didi Nur Hilal; Koyriyah Koyriyah; Ayu Safitri (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This research is motivated by the fundamental obstacles faced by mild intellectually disabled students in mastering prayer practices due to deficits in working memory and sequential thinking skills. The main problems include dependence on verbal instructions and low memory retention of movement sequences. This study aims to analyze the implementation of visual scaffolding media as a cognitive scaffold at SLB Mutiara Bunda Cirebon. The research method used is descriptive qualitative. The results showed that the use of permanent visual cues was able to reduce students' cognitive load and minimize prompt dependency. Through the fading strategy, students showed an increase in independence and order of movement sequences (tumakninah). The integration of this media is proven effective in bridging the transition from full guidance to worship independence